BENZOPHENONE GLUCOSIDE ISOLATED FROM THE ETHYL ACETATE EXTRACT OF THE BARK OF MAHKOTA DEWA [Pha/eria macrocarpa (Scheff.) Boerl.) AND ITS INHIBITORY ACTIVITY ON LEUKEMIA L1210 CELL LINE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT Isolation and elucidation of benzophenone glucoside from ethyl acetate extract of Phaleria macrocarpa bark and its inhibitory activity test against leukemia L 1210 cel/line have been done. The Phalaria macrocarpa bark were maceratedusing n-hexane,ethyl acetate, and ethanol,respectively.The ethyl acetate extract was then chromatographedon silica gel column and gradientlyeluted by n-hexane - ethyl acetate - ethanol with the composition from 20:1:0 until 0:0:1, gave eight fractions. Separation of fraction 6 using semipreparative HPLC on reverse phase column (Capeel/ Pak C-18 SG120, 15 mm I.D. x 250 mm) using methanol- water (40:60, 5 mUmin) gave a brown powder, with the melting point of 182.3 "C. Spectroscopic analysis and comparison of its physicochemical data, this compound was clarified as 2,4'-dihydroxy-4-methoxy~nzophenone-6-0-P.D-glucopyranoside (3). Inhibitory activity of its compound against leukemia L1210 cel/line showed that this compound exhibited inhibitory activity with IC50 was 5.1pg/mL.